IMAGE GENERATOR´S IMPACT ON STUDENT - PILOT´S VISUAL APPROACH ON SIMULATION TRAINING DEVICE (Perner's Contacts, 2015)
Real visual motion has a significant impact on pilot-student during its flight training on simulation device. Therefore, the research is based on the comparison of two different image generators in order to evaluate their performance during the same flight conditions. The results of research will be helpful for further suggestion of future improvements related to image generators in order to ensure the best option for real external image of terrain that is essential for safe flight.
Keywords: image generator, visual approach, simulation training device